Model‐based accuracy enhancements for guarded conductivity measurements: determination of effective electrode areas utilising numerical field simulation. Issue 3 (1st September 2018) - Freye, Claudius; Jenau, Frank
Abstract : Methods utilising current measurements for conductivity and permittivity determination require precise knowledge of the effective electrode area in order to obtain accurate results. Owing to field distortions (e.g. caused by fringing) in guarded electrode setups, the effective electrode area differs significantly from the geometrical calculated. Focusing on guarded electrode setups for conductivity determination, a generic method based on numerical field simulation is presented allowing a convenient determination of the relevant effective electrode area. For this purpose, a brief overview of yet existing normative guidelines and related research work is provided. State‐of‐the‐art conductivity measurement setups are presented in order to identify parameters which affect the field distribution within the measurement arrangements. The description of the implemented method and its realisation in COMSOL multiphysics is followed by its validation using analytical fringing calculations. Furthermore, presented method is used for the evaluation of fringing effects and additional field distortion caused by design aspects of the measurement cell itself and potential imbalances related to the measurement setup. Moreover, dependencies on conductivity of the surrounding environment are considered. Achieved model‐based accuracy enhancements are calculated and are leading to a gain in precision for conductivity determination of up to 25% compared to yet existing approaches.